Malaria and associated co-morbidity in children admitted with fever manifestation in Western Ghana: A retrospective study - Verner N Orish; Joseph Y Ansong; Isaac B Anagi; Onyekachi S Onyeabor; Adekunle O Sanyaolu; Nnaemeka C Iriemenam (Journal of Infection in Developing Countries)
Introduction: Children under five years of age are highly vulnerable to malaria infection and often face dire consequences such as severe malaria if they are not promptly and adequately treated with effective anti-malarial medications. We set out to evaluate malaria and associated co-morbidity among children admitted with febrile illness in Sekondi-Takoradi, Ghana. Methodology: This retrospective study focused on children admitted with fever over a three-year period at the pediatric unit of Effia-Nkwanta Regional Hospital. The children were identified, and the medical records of those who were successfully treated and discharged were searched, retrieved, and reviewed. Results: A total of 1,193 children were identified and selected for analysis. The mean duration of admission increased from 2.17 days in 2010 to 3.36 in 2012. Conversely, the mean age decreased from 3.85 years in 2010 to 2.74 in 2012. Overall, laboratory-confirmed malaria prevalence decreased; however, this decrease was only observed among children five years of age or younger, while malaria prevalence increased among children one year of age or younger. The proportion of children with severe malarial anemia significantly increased, while the proportion of those with mild malaria decreased significantly. Conclusions: Despite the general decrease in malaria morbidity seen in this study, children younger than one year of age remain at increased risk of malaria morbidity. With an increase in malaria prevalence among children younger than one year of age over the three years of study, integrated and targeted control measures are highly needed for this age group.